1984
DOI: 10.1029/ja089ia06p03747
|View full text |Cite
|
Sign up to set email alerts
|

Power spectral signatures of interplanetary corotating and transient flows

Abstract: Recent studies of the time behavior of the galactic cosmic ray intensity have concluded that long term decreases in the intensity are generally associated with systems of interplanetary flows that contain flare‐generated shock waves, magnetic clouds, and other transient phenomena. In this paper the magnetic field power spectral signatures of such flow systems are compared to power spectra obtained during times when the solar wind is dominated by stable corotating streams that do not usually produce long‐lived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 38 publications
0
21
1
Order By: Relevance
“…A 1/f spectrum was also found in observations of the magnetic field strength at low frequencies in the solar wind at 1 AU (Matthaeus et al 1983;Goldstein et al 1984). Matthaeus et al (1983) attribute the 1/f spectrum observed at low frequencies in spectrum of magnetic field strength fluctuations at 1 AU as a signature of the early evolution of turbulence in the solar wind.…”
Section: Spectrum Of Sd(t)mentioning
confidence: 60%
“…A 1/f spectrum was also found in observations of the magnetic field strength at low frequencies in the solar wind at 1 AU (Matthaeus et al 1983;Goldstein et al 1984). Matthaeus et al (1983) attribute the 1/f spectrum observed at low frequencies in spectrum of magnetic field strength fluctuations at 1 AU as a signature of the early evolution of turbulence in the solar wind.…”
Section: Spectrum Of Sd(t)mentioning
confidence: 60%
“…On the other hand, Voyager 1 and 2 observations in the interval July to December, 1982 show that essentially the same long--term (s 6 months) changes in cosmic ray intensity can be produced by distinctly different magnetic field configurations, suggesting that there are some general features of flow systems that are important, as discussed by Burlaga et al (1984a) and Burlaga and Goldstein (1984). Goldstein et al (1984) have identified some differences in the magnetic field spectra of The spectra were computed from one hour average data using the Blaclanan-Tukey method with 20 degrees of freedom, without detrending or filtering the data. Details of this approach are given in Matthaeus and Goldstein (1982).…”
Section: Magnetic Field Spectra and Turbulencementioning
confidence: 84%
“…It would be worthwhile to examine the previous heliosheath data for such a spectrum. An f −1 spectrum of B was observed in the solar wind near the Sun (Matthaeus et al 1982, and Goldstein et al 1984, but not in the distant supersonic solar wind. An f −1 spectrum associated with the microscale fluctuations of dSD1was observed in the heliosheath by V1 during 2009 (Burlaga & Ness 2012a, 2012b).…”
Section: Large-scale Fluctuations Of the Magnetic Field Intensitymentioning
confidence: 94%